The synthesis of steroidal-based anion receptors and analysis of their binding properties - Broderick, Shane (Trinity College (Dublin, Ireland). School of Chemistry, 2000)
Chapter one is an introduction to molecular recognition and supramolecular chemistry; their origin and the history of their progress in recent years. It includes a brief account of the factors that must be considered when designing a receptor for anion recognition. This is followed by a discussion of the most important advances in this area published to date. The discussion is presented in four sections divided according to the type of bonding interactions predominantly exploited by the receptor. This chapter concludes with a description of the aims of the project. Chapter two outlines the first synthesis of a sulfonamido bis-carbamate derivative of methyl cholate synthesised by Justin Perry. This is followed by an alternative method of synthesis for this type of compound that can result in higher yields and allows easier to purification. The lipophilicity of these compounds is increased by derivatising the ester side chain of the host to ensure a full recovery of the receptor after analysis. Chapter three discusses the various receptors made using this novel route outlined in chapter two. Their potency as anion receptors is analysed using the technique of NMR titration with a range of tetrabutylammonium halides. Chapter four discusses new methods for analysing the ability of the receptors to bind anions. Three different techniques are discussed and they all give an insight into the strength of host-guest binding. Chapter five deals with the tris-amino analogue of methyl cholate synthesized by Robert Williams. Some of the physical and chemical properties of this compound are investigated here. Finally, the synthesis of the tris-sulfonamide analogues and their selectivity for chloride over bromide is discussed. Chapter six presents an overall conclusion of the work done in this thesis. Chapter seven contains the experimental details.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin